Application 0f the Problem Based Learning Model in Improving Class I Mathematics Learning Outcomes - Wulandari, Heni (Universitas Sebelas Maret, 2022)
This study aims to improve student learning outcome in the material Recognizing Flat Shapes Class I by applying the Problem Based Learning learning model.This study used the Classroom Action Research (PTK) method which consisted of several cycles. Each cycle consists of 4 steps, namely: planning, implementing, observing and reflecting. The data analisys technique used is descriptive using percentage techniques to see trends that occur in learning activities. The results of this study are the percentage of students who complete the per-cycle 42.86% with a class average of 60. Cycle are 71.43% with a class average of 68.57 and cycle II is 100% equal to ≥ 80% of the indicators determined. These results indicate the application of the Problem Based Learning model can improve students learning outcomes in Mathematics class I semester I SD Negeri 02 Jatiharjo.